Transformasi Plasmid pTRLI ke dalam Protoplas Aspergillus terreus dengan Penambahan Polietilenglikol - DUDI HARDIANTO; MARLIA SINGGIH; AMIR MUSADAD; WAHONO SUMARYONO; TUTUS GUSDINAR (JURNAL ILMU KEFARMASIAN INDONESIA, 2012)
Plasmid transformation is the introduction and incorporation of exogenous plasmid into cells or protoplast. The purpose of this research is transformation of pTRLI plasmid into protoplasts of Aspergillus terreus and obtain stable transformants. The research was initiated by isolation of pTRLI plasmid and determining its purity and concentration by nanodrop machine. Furthermore, protoplasts of A. terreus were isolated enzymatically by addition of chitinase, cellulase, and maserozyme enzymes. pTRLI plasmid was transformed into protoplasts of A. terreus by addition of calcium chloride and polyethyleneglycol (PEG) solutions. These transformants were grown in Czapek-Dox agar medium containing pyrithiamine 1 mg/L and the number of transformants/µg of pTRLI plasmid was calculated. The number of transformants were produced ranging from 12 to 19 transformants/µg of pTRLI plasmid. The success of the transformation was indicated by ptrA gene in transformants that could be amplified by PCR of 801 base pairs in size. It was concluded that PEG solution could be used to transform pTRLI plasmid into protoplasts of A. terreus and transformants are stable up to live generations by growing the transformants in Czapek-Dox agar medium containing pyrithiamine 1 mg/L.